PRINSIP DEBT FORGIVENESS DALAM PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) - Widhi W.S., Ni Komang; Dunia, Ngakan Ketut; Darma Kusuma, A.A. Gde Agung (Kertha Wicara : Journal Ilmu Hukum, 2013)
Forgiveness of debt principle is a principle of law that can be used to lighten theburden to be borne by the debtor as a result of financial difficulties by providing theforgiveness of debts to be clear so that the debtor can resume its business without theburden of old debts (fresh starting) as a breakthrough besides PKPU bankruptcy shouldbe able to protect and create a balance against the debtor and creditors. Therefore, thisarticle will explain whether the principle of starting with a fresh debt forgiveness can beenacted in PKPU.
Keywords: Debt Forgiveness Principle, Fresh Starting, Suspension Of Payment.